2019
DOI: 10.1096/fj.201900925r
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ALP and MMP9 activity facilitates invasive behavior in heterogeneous human BMSC and HNSCC 3D spheroids

Abstract: Mesenchymal stem cells (MSCs) are multipotent progenitor cells capable of differentiating into adipocytic, osteogenic, chondrogenic, and myogenic lineages. There is growing evidence that MSCs home into the tumor microenvironment attracted by a variety of signals such as chemokines, growth factors, and cytokines. Tumor‐homing stem cells may originate from bone marrow–derived MSCs (BMSCs) or adipose tissue‐derived MSCs. Recent scientific data suggest that MSCs in combination with tumor cells can either promote o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 55 publications
7
32
1
Order By: Relevance
“…Similar to our results, they did not observe signi cant effects of hDPSC-derived conditioned medium (CM) on in vitro HNSCC proliferation and therapeutic sensitivity, and in vivo tumour growth, despite the increase in tumour VEGF secretion(45). Con icting results on the impact of other MSC subtypes on in vitro and in vivo HNC cell proliferation, survival, migration, invasion and therapeutic sensitivity have previously been described(46)(47)(48)(49)(50)(51)(52)(53). These effects are mediated in a direct way via differentiation ofMSCs into malignant cells (54, 55), cancer-associated broblasts (CAFs) (56) and vascular-related cells (57, 58), or indirectly by (paracrine) interaction with immune cells (27, 59, 60), cancer stem cells (CSCs) (61-63), endothelial cells (24, 28, 64) and tumour cells (24, 30, 31, 65).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our results, they did not observe signi cant effects of hDPSC-derived conditioned medium (CM) on in vitro HNSCC proliferation and therapeutic sensitivity, and in vivo tumour growth, despite the increase in tumour VEGF secretion(45). Con icting results on the impact of other MSC subtypes on in vitro and in vivo HNC cell proliferation, survival, migration, invasion and therapeutic sensitivity have previously been described(46)(47)(48)(49)(50)(51)(52)(53). These effects are mediated in a direct way via differentiation ofMSCs into malignant cells (54, 55), cancer-associated broblasts (CAFs) (56) and vascular-related cells (57, 58), or indirectly by (paracrine) interaction with immune cells (27, 59, 60), cancer stem cells (CSCs) (61-63), endothelial cells (24, 28, 64) and tumour cells (24, 30, 31, 65).…”
supporting
confidence: 89%
“…The number of previous studies on the safe use of DPSCs as HNC therapy is limited to Hanyu et al (52,53). Therefore, further (long-term) in vivo studies are required to assess whether DPSCs also not interfere with other parameters of HNSCC aggressiveness, including metastasis, invasion and therapeutic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Density gradient centrifugation to isolate BMSCs was used according to established protocols. Afterward, cells were expanded (passage/P 1–3) in growth medium (StemMACS MSC Expansion Medium, #130091680, Miltenyi Biotec, Bergisch Gladbach, Germany) supplemented with 0.2% MycoZap TM Plus-PR (#VZA2022, Lonza, Basel, Switzerland) ( Leyh et al, 2014 ; Wessely et al, 2019 ). Human MSC-associated markers CD73 + , CD90 + , CD105 + , CD19 – and CD34 – were verified via flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…Type IV and V collagens are the major substrates for MMP9. A large number of studies have proved that MMP9 plays an important role in tumorigenesis, proliferation, apoptosis, invasion, and angiogenesis as well [54][55][56][57]. Moreover, it has been reported that the expression and activation of MMP9 are regulated by multiple signal pathways, such as STAT3 pathway [58,59], JNK pathway [60,61] and PI3K/AKT pathway [62].…”
Section: Discussionmentioning
confidence: 99%